Postsecondary Education Students with Disabilities' Perceptions of Occupational Therapy-Led Coaching - Erin E Harrington; Gabriella O Santos; Marie-Christine Potvin (Scholarworks @ WMU, 2021)
Background: Students with disabilities attending postsecondary education (PSE) institutions have poor degree progression, retention, and graduation rates. PSE institutions are addressing these challenges in various ways, including the delivery of occupational therapy (OT)-led coaching. There is emerging evidence that coaching increases academic success and self-determination in PSE. The students' perspectives about the benefits of OT-led coaching intervention has yet to be explored. Method: A phenomenological study was conducted using transcribed semi-structured interviews with 18 college students with disabilities. Qualitative data analysis was conducted through an immersive inter-coder process that included independent coding, comparison of codes, discrepancy resolution to combine or redefine codes, and theme identification. Results: Overall, the participants reported perceiving the OT-led coaching intervention as beneficial to them. Specifically, four major themes emerged from the data: the personal and academic growth achieved, the benefits of an open and supportive environment in the coaching program, the participants' perception of self-identified goal achievement, and the importance of accountability and engagement. Conclusion: The students with disabilities perceived that the OT-led coaching intervention was beneficial and identified aspects of the intervention that were most useful to them, including the emotional and material support.